Totally 3D endoscopic aortic valve replacement: initial results and experience from a single center - Nguyen, Huu Cong; Pham, Dat Thanh (Frontiers in Cardiovascular Medicine, 2024)
Objective This study aimed to evaluate the feasibility and initial outcomes of totally endoscopic aortic valve replacement (TEAVR) performed via a single working port at the fourth intercostal space (ICS) utilizing a 3D endoscopic system. Methods A retrospective observational study was conducted on 35 consecutive patients who underwent TEAVR over a six-month period from December 2023 to June 2024. Patient selection was based on the presence of isolated aortic valve disease without the need for ascending aorta replacement or aortic root enlargement. A 4 cm single working port was created at the 4th ICS, extending from the right mid-axillary to the anterior axillary line. A 10-mm trocar for a 3D endoscope was placed at the right anterior-axillary line. Peripheral cardiopulmonary bypass (CPB) was established. The primary outcomes investigated included the success rate of the procedure, in-hospital mortality, and perioperative complications. Results The mean age of the patients was 58.7 ± 12.8 years, with 22.9% being female. The majority of patients (77.1%) presented with aortic stenosis, often accompanied by severe calcification. The medianCPB time was 210 ± 43 min, and the median aortic cross-clamp time was 132 ± 41 min. The procedure was successfully completed in all patients using the endoscopic approach, with no conversions to full sternotomy. Two mortalities were recorded, attributed to postoperative complications including bleeding and cerebral infarctions. The early (30-day) mortality rate was 5.7%. Prolonged mechanical ventilation (>48 h) was required in 17.1% of patients, and reoperation for bleeding was necessary in 2.9% of patients. Conclusions TEAVR is a feasible procedure with the potential to replace the traditional sternotomy approach for aortic valve replacement.